2017
DOI: 10.1007/s10339-017-0827-4
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory integration and age-dependent sensitivity to body representation modification induced by the rubber hand illusion

Abstract: The results indicated that when visuo-tactile stimuli synchronously presented, the gain in multisensory integration decreased in seniors group. In contrast, in the case of visuo-proprioceptive synchronous presentation, the efficiency of multisensory integration remained unchanged across the lifespan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 72 publications
3
16
2
Order By: Relevance
“…The authors found a decreased subjective feeling of ownership and a greater proprioceptive drift with increasing age. Similar results were shared by another study using the classical RHI paradigm [ 14 ], in which the subjective feeling of ownership decreased with age while proprioceptive drift remained stable. Neither study, however, systematically addressed the three main stages of adult life, i.e., youth, middle age, and older adulthood.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…The authors found a decreased subjective feeling of ownership and a greater proprioceptive drift with increasing age. Similar results were shared by another study using the classical RHI paradigm [ 14 ], in which the subjective feeling of ownership decreased with age while proprioceptive drift remained stable. Neither study, however, systematically addressed the three main stages of adult life, i.e., youth, middle age, and older adulthood.…”
Section: Introductionsupporting
confidence: 85%
“…Three recent studies tried to tackle the issue of age-related changes in the RHI [ 13 , 14 , 15 ]. Graham and colleague [ 13 ] used a modified version of the classical RHI paradigm (i.e., the projected RHI) in a sample aged between 20 and 60 years old.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the hand might not have a high emotional salience, whereas previous studies considered body parts that are among the most unsatisfying in both obesity and healthy weight, such as the abdomen, the thigh, and the buttocks. Finally, it must be noted that Mölbert and colleagues’ (2016) work focused on children and adolescents, whose body representation is still under development and, thus, particularly malleable and unstable (Bremner et al, 2013; Kállai et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Some experimental studies using the “rubber hand illusion” (RHI) (i.e., the prototypical paradigm of the class of bodily illusions, full-body illusion included 23 ) have reported that children show a larger proprioceptive drift toward the fake hand in comparisons with young adults, 24 , 25 but this difference is not mirrored in their explicit feeling of ownership. 24 Kállai et al 26 recently found that old participants (mean age: 65.9 years old) reported less vivid ownership toward the rubber hand compared with younger participants (mean age: 27.7 years old).…”
Section: Discussionmentioning
confidence: 99%